A-Frame free Vascularized Fibular Graft and Femoral Lengthening for Osteosarcoma Pediatric Patients. Issue 2 (February 2018) - Cashin, Megan; Coombs, Christopher; Torode, Ian
Abstract : Background: Pediatric limb reconstruction after resection of a malignant tumor presents specific challenges. Multiple surgical techniques have been used to treat these patients. This paper describes a staged surgical technique for the reconstruction of large distal femoral defects due to tumor resection in skeletally immature patients. Methods: Three pediatric patients with osteosarcoma of the distal femur underwent staged reconstruction. Neoadjuvant chemotherapy was followed by en bloc tumor resection and immediate reconstruction of the distal femoral defect with a vascularized free fibular autograft utilizing a unique A-frame construct combined with intramedullary nail fixation. The second stage was a planned gradual lengthening of the healed construct, over a custom-made magnetically driven expandable intramedullary nail. Results: All patients achieved bony union and satisfactory length with minimal complications. The patients all returned to full, unlimited physical activities. Conclusions: The early results confirm that the described technique is a safe and reliable procedure for the reconstruction of large femoral defects in pediatric patients with osteosarcoma. Level of Evidence: Level IV—therapeutic.